Optimized water allocation with managed groundwater recharge and prioritized wetland deliveries to moderate human-nature water use tradeoffs under climate change - Liying Li; Mustafa S. Dogan; Mahesh Maskey; José M. Rodriguez-Flores; Kellie B. Vache; Spencer Cole; Sarah E. Null; Joshua H. Viers; Mohammad Safeeq; Josue Medellin-Azuara; Martha Conklin (Journal of Hydrology: Regional Studies)
Study region: California, United States. Study focus: In California, historical water system channelization disturbed the natural water system, making agricultural and wetland deliveries share the same water supply system. Climate change has intensified the competition between agricultural and environmental water uses. In the face of escalated climate change, this study tackles the critical challenge of optimizing water allocation to balance the needs of agriculture and the environment. A landscape-level, implicit stochastic deterministic linear hydro-economic optimization model is used with limited foresight to evaluate the combined impacts of climate change and water management policies on local water allocation decisions in California. The aim is to provide decision-support information for regional water cost-efficient water reallocation for climate change adaptation. New hydrological insights for the region: Climate change has reshaped water allocation ratios and caused agricultural water use to compromise with environmental water use. In water-scarce regions, the reduction of agricultural water use is most prominent in the wet years of the Mediterranean climate when both agricultural and environmental water use demands are high. The research identified when, where, and how much groundwater recharge benefit is acquired from prioritizing wetland deliveries to inform water use co-benefits and moderate conflicts. Climate change has also increased the overall value and variation across areas in the economic value of water, creating momentum for a cost-efficient market-based water reallocation approach.